The unique traits of the subgenus Unicus within Chiasmocleis Méhely, 1094 (Anura: Microhylidae) - de Sá, Rafael O.; Riva Tonini, João F.; van Huss, Hannah; Zaher, Hussam; Haddad, Célio F.B. [UNESP] (Magnolia Press, 2019)
Chiasmocleis is the most speciose genus of Neotropical microhylids. The genus consists of three monophyletic clades that were recently recognized as subgenera. Within Chiasmocleis, the subgenus Unicus has a basal position in the phylogeny and contains a single species that occurs in the North Atlantic Forest of Brazil, isolated from the ranges of other Chiasmocleis. However, the subgenus Unicus lacked a formal description and consequently so far was a nomen nudum. Herein, we provide a diagnosis (i.e., morphological and molecular apomorphies) of the subgenus Unicus de Sá, Tonini, van Huss, Long, Cuddy, Forlani, Peloso, Zaher and Haddad, 2019b; for convenience, the name has also been registered in ZooBank.
Keywords: Apomorphies; Chiasmocleis; Molecular; Morphology; Unicus